Polymorphism, isostructurality and physicochemical properties of glibenclamide salts - Suresh, Kuthuru; Khandavilli, U. B. Rao; Gunnam, Anilkumar; Nangia, Ashwini (CrystEngComm, 2017)
Novel salts of glibenclamide (GBA), namely glibenclamide-sodium (GBA-Na), glibenclamide-potassium (GBA-K) and glibenclamide-ammonium (GBA-NH4) were crystallized under different conditions to obtain their polymorphs, and their aqueous solubility and hydration stability studies are reported. The GBA-Na salt is dimorphic (forms I and II)and also exists as hydrate GBA-Na-H2O (form III). The GBA-K salt exists in anhydrous and hydrate forms (GBA-K, forms I and II). Crystal structure analysis of GBA-Na forms I and II showed differences in geometry of the central metal atom and ligand orientation. This kind of polymorphism of sulfonyl urea salts appears to be novel in the Cambridge Structural Database (CSD). The iso-structurality of GBA-Na form I with GBA-NH4 and GBA-K form I salts is discussed. The potassium salts of GBA exhibited higher solubility compared to pure GBA. Specifically GBA-K salt forms I and II showed higher solubility by 77 fold in the water and 33 fold in phosphate buffer (pH 7) compared to the other salts. Dynamic vapor sorption (DVS) showed reversible water sorption without hysteresis for all salts, except for GBA-K form II which transformed to form I after a sorption and desorption cycle as confirmed by PXRD.